Outcome of children with Langerhans cell histiocytosis and single-system involvement: A retrospective study at a single center in Shanghai, China. (17th November 2018) - Su, Meng; Gao, Yi-Jin; Pan, Ci; Chen, Jing; Tang, Jing-Yan
Abstract: Background: This is a descriptive review of the clinical patterns and outcomes of children with Langerhans cell histiocytosis and single-system involvement (SS-LCH) treated at Shanghai Children's Medical Center. Procedure: 60 evaluable newly diagnosed patients (37 boys, 23 girls) with a median age of 3.9 years (range: 0.3–15.3 years) and histiopathology-confirmed SS-LCH were enrolled from 2010 to 2014. All patients received systemic chemotherapy using either the DAL HX-83 or LCH-II protocol as determined by the physician. Results: Bone was the most frequently affected organ (56/60, 93.3%). Of the 56 patients suffering from SS-bone disease, 35 (62.5%) had unifocal disease and 21 (37.5%) had multifocal disease. CNS-risk lesions were seen in nine patients (16.1%, 9/56) at diagnosis. Thirty-two patients were treated with the LCH-II protocol and 28 received the DAL HX-83 protocol. No patient received intralesional steroid injection at the time of surgery. CNS-risk lesion correlated with an inferior event-free survival (EFS) for patients with bone disease (62.5 ± 17.1% vs. 90.7 ± 4.5%; p = 0.039). The difference in the 5-year EFS between patients with unifocal and multifocal SS-bone LCH did not reach the statistical significance (93.8 ± 4.3% vs. 75.0 ± 9.7%; p = 0.074). No deaths were observed, leading to a 5-year OS of 100% in the present cohort of patients. Permanent consequences and secondary malignancies were not observed but were also limited by short follow-up. Conclusions: Optimal therapy for patients with SS-bone LCH has not been established. Less toxic therapeutic approaches should be considered for these patients and tested in prospective trials.